Perancangan Bilah Turbin Angin Jenis Taperless Untuk Pesisir Pantai Utara Jawa Barat Menggunakan Perangkat Lunak QBlade - Shinta Dwi Oktaviani; Reza Setiawan; Farradina Choria Suci (Politeknik Negeri Padang, 2021)
Energy needs in Indonesia continue to increase, while the availability of non-renewable energy sources is decreasing and is exacerbated by the increasing use of fuels that are not environmentally friendly, so efforts are needed to find alternative uses of renewable energy that are renewable and environmentally friendly. The Cirebon coast has good wind conditions which can be used to create renewable energy sources through the wind. This study aims to utilize the energy that is already available by designing a horizontal wind turbine blade. The method used starts from literature study, selecting airfoils, analyzing data, selecting the best airfoils, analyzing the best airfoils and ending with design drawings. The initial data used as the initial design is the Cirebon City wind data which has the highest average wind speed of 9 m/s. This study designed a horizontal wind turbine blade using QBlade Software with 3 types of NACA, NACA 4415, 6412 and 6415. NACA 6415 has a power coefficient of 0.40%, the highest coefficient is then obtained NACA 6412 with a coefficient of 0.41%, and The highest power coefficient was obtained by NACA 4415 with a coefficient of 44%